Analisis Strategi Pengembangan Bisnis Rumah Makan Wong Solo Di Kendari - Rahmawati, Fitrah; bake, jamal; Purwati, Ninik Endang (Universitas Halu Oleo, 2018)
This Research aim to to know the strategy of development of Restaurant business Wong Solo in Kendari. Informan in this research that is perpetrator of is effort restaurant of Wong Solo consisted of by the head of is effort and other employees as much 5 people. Technique of data collecting used by is interview mendalam, dokumentasi. Research method used by is descriptive approach analyse with the approach qualitative with the research process of through/ passing permanent measurement by means of that is matrix SWOTResult of this research indicate that the: strategy of development of business of restaurant of Wong Solo that is strategic location determination by exploiting reliable human resource management is its area is elementary substance election goodness and also product processing becoming especial menu with the goal feel typical and also the make-up of service, taking care of security and kenyamantehadapcutomer/ client. S0 that born the prima service strategy with the method Greeting. Greeting is expression or greet with the method: 1) greeting guest with the greeting of according to company standard, 2) smile the heartfelt, 3) bring the guest clothes that have been provided according to the number of guests.ABSTRAK Penelitian ini bertujuan untuk mengetahui strategi pengembangan bisnis Rumah Makan Wong Solo di Kendari. Informan dalam penelitian ini yaitu pelaku usaha rumah makan Wong Solo yang terdiri dari pimpinan usaha dan karyawan lainnya sebanyak 5 orang. Teknik pengumpulan data yang digunakan adalah wawancara mendalam, dokumentasi. Metode penelitian yang digunakan adalah pendekatan deskriptif analisis dengan pendekatan kualitatif dengan proses penelitian melalui pengukuran dengan alat yang baku yaitu matriks SWOT.Hasil penelitian ini menunjukkan bahwa :strategi pengembangan bisnis rumah makan Wong Solo yaitu penentuan lokasi yang strategis dengan memanfaatkan manajemen sumberdaya manusia yang handal dibidangnya baik pemilihan bahan dasar maupun pengolahan produk yang menjadi menu utama dengan cita rasa yang khas serta peningkatan layanan, menjaga keamanan dan kenyaman terhadap pelanggan. Sehingga lahirlah strategi pelayanan prima dengan metode Greeting. Greeting adalah ungkapan sambutan atau salam dengan metode: 1) menyambut tamu dengan sambutan sesuai standar perusahaan, 2) senyum dengan tulus, 3) mengantar tamu kemeja yang sudah disediakan sesuai dengan jumlah tamunya.